PRELIMINARY STUDY ON PERFORMANCE OF Zn-DOPED ZEOLITE IN LOW-TEMPERATURE CO2 ADSORPTION - Ang Gaun Yu,; Zhi Hua Lee,; Chee Yung Pang,; Gulnaziya Issabayeva, (Malaysian Journal of Science, 2024)
Zeolite has been identified as a potential low-temperature CO₂ adsorbent with the highest adsorption capacity among adsorbents in its category. However, its adsorption capacity remains relatively low, limiting its industrial application for CO₂ adsorption. Additionally, there is a need to increase the optimal adsorption temperature of this porous material to effectively adsorb CO₂ emitted from flue gas, which has an average temperature of 100 - 125°C. To address these challenges, a preliminary study on Zn-doped zeolite has been conducted. This study aims to investigate the ability of Zn-doped zeolite to enhance CO₂ adsorption capacity and its effect on the optimal temperature for CO₂ adsorption. Zinc-doped zeolite was synthesized by doping zinc oxide into natural zeolite using a zinc ion exchange method at different doping concentrations (0.2 M & 1.0 M). Undoped natural zeolite was studied as a benchmark. Their CO₂ adsorption performance was tested using TGA at 30°C, 50°C, and 100°C. The effects of temperature and doping concentration on adsorption capacity were investigated. The adsorbent samples were characterized using X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray (EDX) analysis. It was found that increasing the temperature from 30°C to 50°C increased the CO₂ adsorption capacity, but the capacity decreased when the temperature was further increased to 100°C. Furthermore, increasing the doping concentration tended to enhance the CO₂ adsorption capacity. The highest adsorption capacity of 0.0281 g CO₂/g sorbent was observed in zinc-doped zeolite with a 1.0 M doping concentration at 50°C. The improvement was mainly attributed to the zinc oxide doped on the zeolite, which provided a functional group that formed chemical bonds with CO₂. This study also found that the adsorption rate of CO₂ was predominantly influenced by temperature, while the effect of doping concentration was less significant. All testing and characterization results suggested that the zinc-ion exchange method improved the CO₂ adsorption capacity of zeolite.